2006
DOI: 10.1063/1.2167788
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency blue light-emitting electrophosphorescent device with conjugated polymers as the host

Abstract: Highly efficient blue polymer phosphorescent organic light-emitting diode ͑PPHOLED͒-containing iridium͑III͒ bis ͑2,4-difluorophenyl-2-pyridine͒ ͑2-͑4H-1, 2, 4-triazol-3-yl͒pyridine͒ ͓Ir͑PPF͒ 2 ͑PZ͔͒ complex embedded into wide-gap poly ͑9,9Ј-alkyl-3, 6-silafluorene͒ ͑PSiFC6C6͒ has been fabricated. Despite the significant quenching of photophosphorescence emission of the iridium complexes by a PSiFC6C6 host polymer, organic light-emitting diodes containing Ir͑PPF͒ 2 ͑PZ͒ doped into the polymer host PSiFC6C6 emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 19 publications
(10 reference statements)
3
44
0
Order By: Relevance
“…That is to say, FIrpic was completely quenched even at high doping concentrations. Similar quenching phenomena have been observed before for conjugated polymers [20,21,23]. Previous studies showed that the lower triplet energy level of the polymer host would cause energy back transfer from phosphorescent dye to polymer, leading to phosphorescent quenching [20,21,[23][24][25].…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…That is to say, FIrpic was completely quenched even at high doping concentrations. Similar quenching phenomena have been observed before for conjugated polymers [20,21,23]. Previous studies showed that the lower triplet energy level of the polymer host would cause energy back transfer from phosphorescent dye to polymer, leading to phosphorescent quenching [20,21,[23][24][25].…”
Section: Methodssupporting
confidence: 60%
“…Similar quenching phenomena have been observed before for conjugated polymers [20,21,23]. Previous studies showed that the lower triplet energy level of the polymer host would cause energy back transfer from phosphorescent dye to polymer, leading to phosphorescent quenching [20,21,[23][24][25]. A schematic diagram of the energy levels for PFO, FIrpic and PVK is displayed in Figure 2. Since the triplet energy level of PFO (2.3 eV) [20] is lower than that of FIrpic (2.65 eV) [26], energy back transfer occurs from the triplet excitons on the FIrpic to the low-lying triplet states of PFO that causes the FIrpic quenching.…”
Section: Methodsmentioning
confidence: 49%
“…Cao and coworkers also observed an interesting phenomenon whereby the PL spectrum of the polymer/iridium blend showed emission from the polymer only while the EL spectrum showed emission from the iridium complex alone (Fig. 4) [47]. This difference in PL and EL spectra was attributed to a Förster transfer mechanism in the PL process in contrast to a charge trapping mechanism in the EL process.…”
Section: Organic Electronic Devicesmentioning
confidence: 91%
“…No emission was detected from the polymer indicating complete energy transfer from the polymer host to the green dopant. Cao and coworkers reported a similar system with a blue phosphorescent iridium dopant [47]. In comparison with the use of polyvinylcarbazole (PVK) as the polymer host, poly(3,6-dibenzosilole) 36 devices gave much higher external quantum and luminous efficiencies.…”
Section: Organic Electronic Devicesmentioning
confidence: 96%
See 1 more Smart Citation